Anomalous 96Zr resonance integral to thermal activation cross-section ratio and the neutrón activation resonance integral of 94Zr and 96Zr - Ricabarra, M. O.; Ricabarra, G. H.; Faradjie de Turjanski, Rosa (1970)
Fil: Ricabarra, M. O. Comisión Nacional de Energía Atómica; Argentina